An apparatus for tilling soil. - Ahmad, Desa (2010)

(untitled)
An apparatus that combines a disk plough, also known as a main disk, a rotary blades to prepare a seedbed and bury crop residues has been invented. The combination of disk plough and rotary blades apparatus of this invention is able to reduce energy consumption in tillage, soil compaction and structural degradation. Vehicular traffic and machine cost is therefore reduced, as the current multi-pass tillage treatments are replaced by a single pass when using the apparatus of the present invention.